Supplementation alimentaire des boeufs de labour du systeme agropastoral du mil a Dalonguebougou: resultats preliminaires - Traoré, A.; Soumare, S. (CIPEA, 1984)
Presents findings of a study carried out at Dalonguebougou in Mali to examine the effects of supplementary feeding with cowpea haulms on the maintenance and work output of draft oxen.